Application of 3D-Printed Patient-Specific Titanium Plate in Mandibular Cyst Surgery: A Case-Based Approach - Aktaş, Hasan (2026)
Pathological lesions such as cysts and tumors can significantly weaken the mandible, increasing the risk of pathological fractures during or after surgical removal. Preventive osteosynthesis using patient-specific plates (PSPs) has emerged as a reliable method to enhance mandibular stability in such cases. The intraoperative use of these plates may be considered in patients at elevated fracture risk, as demonstrated in the present case. A 67-year-old woman was detected with a well-defined unilocular radiolucent lesion in the right posterior mandible during a routine dental examination. Cone-beam computed tomography revealed a lesion measuring 24.0 × 11.6 × 24.6 mm, extending to the base of the mandible. Enucleation of the lesion was planned, with a preoperative decision to use a patient-specific titanium plate due to the high fracture risk. Virtual surgical planning (VSP) was performed using CBCT data, and a customized plate was fabricated using 3D printing technologies. During surgery under general anesthesia, the cyst was enucleated, and the PSP was fixed at the planned location. The patient was followed up during the first week, second week, first month, and eighth month. Postoperative healing was uneventful, with resolution of transient hypoesthesia and confirmed plate positioning on follow-up imaging.This case suggests that the application of a patient-specific plate, guided by virtual planning and three-dimensional modeling, may help reduce the risk of pathological fracture during mandibular surgery, while allowing for more precise plate adaptation and stable postoperative outcomes.